(untitled) (Jurnal Adabiya, 2025)
The pinnacle of Aceh’s political and cultural prosperity occurred during the reign of Sultan Iskandar Muda (1607–1636), who implemented structural reforms through the Qanun Meukuta Alam, a royal legal code regulating socio-cultural order, law, and governance. This Qanun reflects a synergy between Ulama and Umara, two key elements of Islamic leadership in Aceh. This study employs a descriptive qualitative method, with data collected through library research. To address the two main issues of this study namely, the nature of the relationship between Ulama and Umara within the Qanun Meukuta Alam and how the structure of the kingdom supported this relationship the study applies Talcott Parsons’ Structural Functionalism theory, focusing on the AGIL framework. The findings based on the AGIL analysis indicate that the adaptation process undertaken by Sultan Iskandar Muda as Umara involved incorporating Ulama as partners in governance and appointing the Panglima Polem as the holder of formative authority based on the counsel of the Ulama. The goal attainment pursued by the Umara was the implementation of laws grounded in Islamic law (sharia) in order to establish a prosperous society.